A new digital control of four‐leg inverters in the natural reference frame for renewable energy–based distributed generation. (14th February 2019) - Pichan, Mohammad; Rastegar, Hasan; Monfared, Mohammad
Summary: Nowadays, stand‐alone dispersed generation (DG) supplied from renewable energies is rapidly growing. In such a condition, four‐leg inverter can be considered as a successful option to supply unbalanced loads, especially in transformerless systems. In this paper, four‐leg inverter is modeled considering the fourth line inductor. The neutral (fourth) line inductor causes a high coupling through control variables in the natural reference frame. To avoid several transformations among reference frames, a new digital controller based on deadbeat (DB) theory is proposed in the natural reference frame to regulate the load voltages under coupled model. The proposed method offers simplicity, ease of digital implementation, and a fast dynamic response. Furthermore, a delay compensation procedure is also proposed to make the overall performance of the proposed DB controller better. Experimental tests based on a 3kW prototype are implemented to support the analytical analysis. Different tests under various single/three‐phase, nonlinear/linear, and unbalanced/balanced load conditions were performed, which confirm the excellent performance of the proposed control system.